Progressive transformation of immortalized esophageal epithelial cells - Shen, Zhong-Ying (World J Gastroenterol, 2002)
AIM: To investigate the progressive transformation of immortal cells of human fetal esophageal epithelium induced by human papillomavirus, and to examine biological criteria of sequential passage of cells, including cellular phenotype, proliferative rate, telomerase, chromosome and tumorigenicity. METHODS: The SHEE cell series consisted of immortalized embryonic esophageal epithelium which was in malignant transformation when cultivated over sixty passages without co-carcinogens. Cells of the 10th, 31st, 60th and 85th passages were present in progressive development after being transfected with HPV. Cells were cultivated in a culture flask and 24-hole cultural plates. Progressive changes of morphology, cell growth, contact-inhibition, and anchorage-dependent growth characteristics were examined by phase contrast microscopy. The cell proliferation rate was assayed by flow cytometry. The modal number of chromosomes was analyzed. HPV18E(6)E(7) was detected by Western blot methods and activities of telomerase were analyzed by TRAP. Tumorigenicity of cells was detected with soft agar plates cultivated and with tumor formation in SCID mice. RESULTS: In morphological examination the 10th passage cells were in good differentiation, the 60th and 85th passages cells were in relatively poor differentiation, and the 31st passage cells had two distinct differentiations. The characteristics of the 85th and 60th passage cells were weakened at contact-inhibition and anchorage-dependent growth. Karyotypes of four stages of cells belonged to hyperdiploid or hypotriploid, and bimodal distribution of chromosomes appeared in the 31st and 60th passage cells. All of these characteristics combined with a increasing trend. The activities of telomerase were expressed in the latter three passages. Four fourths of SCID mice in the 85th passage cells and one fourth of SCID mice in the 60th passage cells developed tumors, but the cells in the 10th and 31st passage displayed no tumor formation. CONCLUSION: In continual cultivation of fetal esophageal epithelial cells with transduction of HPV18E(6)E(7), cells from the 10th to the 85th passage were changed gradually from preimmortal, immortal, precancerous to malignantly transformed stages. All of these changes were in a dynamic progressive process. The establishment of a continuous line of esophageal epithelium may provide a in vitro model of carcinogenesis induced by HPV.